Modelagem cinética da hidrodesoxigenação do ácido oleico empregando carbeto de molibdênio suportado em alumina - Souza, Mellyssa Soares de (2019)
Triglyceride-based materials are considered to be promising renewable feedstocks for the production of biofuels by hydrodeoxygenation (HDO), which have very similar properties to conventional petroleum fuels. In this work, oleic acid was used as model compound to study the HDO over Mo2C/γ-Al2O3 catalyst, in a fixed-bed reactor at 30 bar pressure. The reaction temperature and the weight hourly space velocity were varied within 260–340 °C and 20–60 h−1 , respectively. The Mo2C/γ-Al2O3 was synthesized in situ by temperature programmed carburation. Liquid samples collected at regular interval of time were identified by GC-MS and quantified by GC-FID. Catalyst performed rather stable, and the steady state of each experiment was achieved after 5–6 h of continuous operation. Higher conversions were achieved with the increased temperature and contact time. A reaction pathways was proposed based on observed products distribution, allowing for the derivation of a kinetic model. The reactions were assumed to be pseudo-first-order with respect to liquid phase components. A method of numerically integrating and trust-region-reflective optimization algorithm with maximum likelihood as objective function were applied and performed in MATLAB®. The confidence intervals of the parameters were estimated under 95% confidence level. The model described well the kinetic data under versatile reaction conditions. The estimation results show a good agreement between the experimentally obtained and predicted concentrations, with correlation coefficient of 87–99%. HDO of oleic acid proceeded via formation of stearic acid and octadecenal as a primary products, octadecanal, octadecenol and octadecanol as oxygenated intermediates, and C17 and C18 hydrocarbons as the final products. Hydrocarbons C18 was significantly more dominant than C17.